Varicella zoster virus DNA in throat swabs. Issue 3 (March 1991) - Ozaki, T; Miwata, H; Matsui, Y; Kido, S; Yamanishi, K
Abstract : Eighty-one throat swabs from 18 patients infected with varicella were tested for varicella zoster virus DNA by the polymerase chain reaction. The positive rates were 26.2% (11/42) during the incubation period and 89.7% (35/39) after clinical onset. The results indicate the pharynx is a site for early replication of the virus.